Effect of diet supplementation on the quality of composts made from faeces, urine and feed refusals - Sangare, M.; Bationo, B. André; Hiernaux, Pierre H.Y.; Fernández Rivera, S.; Pandey, V.S. (Institut de Medecine Tropicale Prince, 2002)
A greenhouse experiment was carried out at the International Crop Research Institute for the Semi Arid Tropics (ICRISAT), at Sadord (13°15' N, 2°18'E), Niger, in conjunction with a feeding trial. Eight types of compost were made with millet stover (refusals and faeces with or without urine from sheep fed millet stover (40 g kg-1 LW), and supplemented with 2 levels of Nitrogen (N) in the form of groundnut cake (0 et 7.5 g kg-1 LW) and 2 levels of phosphorus (0 et 3 g j-1) in the form of single super phosphate (SSP). The addition of urine was accomplished by using millet stover refusals as litter. The composts were analysed for N and P. Their agronomic value was evaluated on a millet crop. Urine addition increased compost N by 11.5 (no P supplemented sheep) and 16 % (P supplemented sheep) and.P by 18 and 26 % respectively, only when sheep were offered groundnut cake supplement. Compost P was multiplied by more than two, with P supplementation, regardless of urine addition or N supplementation. Millet's early growth (15 and 30 days after planting) was affected (P < 0.05) by both N and P supplementation and urine addition, but there was no effect of P supplementation from 45 days after planting (DAP). Nitrogen supplementation, urine addition and the interaction of N supplementation by urine addition increased (P< 0.05) millet aboveground mass at the harvest by 14% and 38 % respectively. Urine addition (+49%) and compost P (+24%) were the major determinants of root mass, but there was no effect of N supplementation on root mass. The apparent efficiency of N use was 47% higher (P < 0.05) in millet amended with composts plus urine than that without urine. It was concluded that bedding animals on roughage refusals prior to composting them is a low input technology that could enhance nutrient cycling in stall feeding systems.